2021
DOI: 10.3389/fphar.2021.751321
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Escitalopram and Paroxetine Intranasal Co-Administration: In Vitro/In Vivo Evaluation

Abstract: Depression is a common mental disorder. Its treatment with selective serotonin reuptake inhibitors (SSRIs) is effective only in a fraction of patients, and pharmacoresistance is increasing steadily. Intranasal (IN) drug delivery to the brain stands out as a promising strategy to improve current therapeutic approaches by operating as a shuttle to overcome the blood–brain barrier. This work aimed to simultaneously administer escitalopram and paroxetine by IN route to mice. For this purpose, three nanostructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Paroxetine belongs to the SSRI class, has low oral bioavailability (less than 50%), and undergoes an extensive first-pass effect. It also has a high potential for drug–drug interactions, especially when used in polytherapy [ 66 ]. To overcome some of these problems, Silva et al [ 66 ] investigated the efficacy of the direct delivery of paroxetine to the brain in combination with another drug, borneol.…”
Section: Successful Approaches To Increasing Brain Targeting and Bioa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Paroxetine belongs to the SSRI class, has low oral bioavailability (less than 50%), and undergoes an extensive first-pass effect. It also has a high potential for drug–drug interactions, especially when used in polytherapy [ 66 ]. To overcome some of these problems, Silva et al [ 66 ] investigated the efficacy of the direct delivery of paroxetine to the brain in combination with another drug, borneol.…”
Section: Successful Approaches To Increasing Brain Targeting and Bioa...mentioning
confidence: 99%
“…It also has a high potential for drug–drug interactions, especially when used in polytherapy [ 66 ]. To overcome some of these problems, Silva et al [ 66 ] investigated the efficacy of the direct delivery of paroxetine to the brain in combination with another drug, borneol. Borneol is a natural compound that has already been shown to be effective in opening channels in the BBB.…”
Section: Successful Approaches To Increasing Brain Targeting and Bioa...mentioning
confidence: 99%
“…In a recent study, escitalopram and paroxetine were co-loaded into NLCs for the treatment of depression [ 111 ]. The optimized NLC formulation was incorporated into a thermoreversible Poloxamer 407 and Carbopol 974P gel.…”
Section: In Vivo Evaluations Of Sln and Nlc-based Formulations For No...mentioning
confidence: 99%
“…In vivo studies showed that intranasal delivery of the drug had similar pharmacokinetic parameters to intravenous administration, whereas escitalopram did not exhibit significant direct nasobrain delivery but reduced exposure elsewhere. In contrast, intranasal delivery of paroxetine-loaded borneol-NLCs significantly increased the concentration in the brain (5-fold), showing good brain targeting [ 122 ].…”
Section: Intranasal Administration Of Antidepressant Active Ingredientsmentioning
confidence: 99%